STANDARDIZATION OF AN AYURVEDIC POLYHERBAL LIQUID FORMULATION WITH IMPROVED PALATABILITY FOR THE MANAGEMENT OF ANEMIA - RAMACHANDRAN, KOPPERUNDEVI; KARUNANITHI, SHALINI; NARAYANASAMY, DAMODHARAN (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to develop and standardize a palatable Ayurvedic polyherbal oral liquid formulation for anaemia treatment. By integrating taste-masking techniques, the aim is to enhance iron absorption, reduce side effects, and improve patient adherence. Methods: Four iron-rich Ayurvedic herbs, namely Punica granatum, Vitis vinifera, Boerhaavia diffusa, and Terminalia bellirica, were extracted and formulated with taste-masking excipients. The syrup formulation involved hydroalcoholic extraction, freeze-drying, and stability testing under accelerated and long-term conditions. Standardization parameters included organoleptic evaluation, physicochemical assessment, microbiological testing, and heavy metal residue analysis. Results: The hydroalcoholic extraction of Terminalia bellirica fruit yielded 17.3%, while Boerhavia diffusa root extract yielded 9.3%. Freeze-dried fruit juices of Vitis vinifera and Punica granatum yielded 8.6% and 7.3%, respectively. A polyherbal syrup was formulated and optimized through six trials, balancing taste, viscosity (120–146 cP), and stability. The final formulation contained 12.5 mg iron per 5 ml, with synergistic herbal components enhancing bioavailability. Sensory evaluations confirmed improved palatability and stability studies demonstrated a prolonged shelf life. Heavy metal analysis confirmed compliance with safety standards, ensuring the formulation's suitability for anaemia management. Conclusion: This Ayurvedic polyherbal liquid formulation, with its enhanced taste profile and iron-rich content, offers a novel and patient-friendly approach to anaemia management. Its improved palatability may enhance patient compliance, particularly in populations struggling with conventional iron supplements. Moreover, its formulation aligns with the growing demand for natural, well-tolerated therapeutic alternatives, underscoring its potential for commercialization. Further clinical studies are recommended to validate its efficacy, long-term safety, and market viability for broader therapeutic application.